Neoadjuvant Chemotherapy for Nonmetastatic Esophago-Gastric Adenocarcinomas: A Systematic Review and Meta-Analysis. (1st July 2013) - Zhang, Chun-Dong; Zeng, Yong-Ji; Li, Hong-Wu; Zhao, Zhe-Ming; Zhang, Jia-Kui; Dai, Dong-Qiu
<x xml:space="preserve">Abstract</x> Objective: A systematic review and meta-analysis was performed to investigate the efficacy of neoadjuvant chemotherapy for nonmetastatic esophago-gastric adenocarcinomas. Methods: Electronic databases were searched systematically from January 1980 to July 2012 and a total of 2, 587 patients from 17 randomized controlled trials were subjected to meta-analysis. The odds ratios (ORs) for overall survival (OS) and progression-free survival (PFS) were calculated. Results: Seventeen randomized controlled trials were obtained and various comparisons of treatment approaches were performed. Randomized controlled trials detected no differences in these comparisons: R0 resection for neoadjuvant chemotherapy versus none; Preoperative chemotherapy versus surgery alone: 3-year OS, 5-year OS, 5-year OS in Europe, 3-year PFS; Preoperative chemotherapy plus postoperative chemotherapy versus postoperative chemotherapy: 1-year OS, 5-year OS; Preoperative chemotherapy versus preoperative chemoradiotherapy: 3-year OS. Randomized controlled trials detected significant differences in these comparisons: Preoperative chemotherapy plus postoperative chemotherapy versus surgery alone: 3-year and 5-year PFS, 5-year OS; Subgroup analysis examining preoperative chemotherapy versus surgery alone: 5-year OS in Asia; Preoperative chemotherapy versus postoperative chemotherapy: 1-year OS. Conclusion: The current limited evidence suggests that preoperative chemotherapy can be applied to patients with nonmetastatic esophago-gastric adenocarcinomas (specifically, advanced esophago-gastric cancer). However, the results should be interpreted with caution because of the statistically low power and the heterogeneity among study designs; therefore, our results need validations in future studies.